HUBUNGAN ANTARA AKTIVITAS MENONTON TAYANGAN TELEVISI DAN INTENSITAS BIMBINGAN ORANG TUA DENGAN PRESTASI BELAJAR SOSIOLOGI SISWA SMA N 1 BANTUL TAHUN PELAJARAN 2012/ 2013 - Nugraha, Yudi Aditya (ISSN.2252-8407)
The objective of research was to find out the significant relationship of: (1) television show watching activity to learning achievement, (2) parent guidance intensity to learning achievement, and (3) television show watching activity and parent guidance intensity to learning achievement in the X graders of SMA N 1 Bantul in the school year of 2012/2013. This study employed a quantitative method with statistic analysis. The population of research was all of the X graders of SMA Negeri 1 Bantul consisting of 192 students. The sample was taken using random sampling. The size of sample for instrument tryout consisted of 17 students, selected randomly, and the sample of research consisted of 49 students. Technique of collecting data used for X1, X2, and Y variables was questionnaire, while the data analysis was conducted using a statistic descriptive analysis and product moment correlation with SPSS program for windows help. Considering the result of research, it could be found (1) the activity of watching television show related with the learning achievement with rX1Y = 0.0149, and P = 0.30, so that the relationship of activity of watching television show to learning achievement of the X graders of SMA N 1 Bantul was not significant. (2) The parent guidance intensity related with the learning achievement with rX2Y = 0.285, and P = 0.045, so that the relationship of parent guidance intensity to learning achievement of the X graders of SMA N 1 Bantul was significant. (3) The relationship of television show watching activity and parent guidance intensity to learning achievement yielded r X1X2Y = 0.339, and P = 0.060, so that the relationship of television show watching activity and parent guidance intensity to learning achievement in the X graders of SMA N 1 Bantul was significant.Keywords: television show watching activity, parent guidance intensity, student learning achievement.